Presentation of HIV and Mtb derived peptides by HLA-E. (October 2022) - Walters, Lucy; Harlos, Karl; Rozbesky, Daniel; Jones, Yvonne; McMichael, Andrew; Gillespie, Geraldine
Abstract : Unconventional, Mamu-E-restricted CD8+ T cell responses directed against a diverse range of epitopes have been implicated as immune correlates of sterile immune protection in rhesus CMV-vectored SIV vaccination. In light of these findings, we have re-explored the peptide binding specificity of the human ortholog, HLA-E, from the view of developing a parallel HIV vaccination strategy in humans. Given the extraordinary breadth of vaccine-elicited, Mamu-E-restricted responses, we first optimised and developed two highly sensitive peptide binding affinity assays to determine whether broad epitope sampling also extends to HLA-E. We found extensive overlap in the binding repertoires of the human and rhesus orthologs, and the majority of SIV-derived Mamu-E-restricted epitopes tested also bound HLA-E. We also demonstrated binding for a number of HIV and Mtb derived epitopes identified from rhesus macaques vaccinated with rhCMV-HIV Gag immunogens or from active tuberculosis infection in humans, respectively. As previous crystal structures of HLA-E were exclusively solved in complex with canonical MHC-I signal peptides, we next investigated the structural basis underlying pathogen-derived peptide binding. We obtained a panel of crystal structures of HLA-E in complex with different epitopes including a number from Mtb in addition to the HIV counterpart to the vaccine-identified SIV Gag 'supertope'69. Strikingly, despite the presence of canonical primary anchor residues, the HIV pep- tide adopted an unusual motif within the peptide binding groove, generating a solvent exposure profile that deviated from canonical signal peptide motifs, with potential implications for T cell receptor recognition and immunogenicity. Further, structural and mutagenesis analyses illustrated a greater tolerance for hydrophobic and polar residues in the primary pockets than previously anticipated. In conclusion, our combined structural and peptide binding data suggest a previously underestimated breadth of the HLA-E peptidome and support the potential for broadly targeted HLA-E-restricted HIV vaccine development.